2022
DOI: 10.1186/s12987-022-00319-x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained glymphatic transport and impaired drainage to the nasal cavity observed in multiciliated cell ciliopathies with hydrocephalus

Abstract: Background Hydrocephalus (increased ventricular size due to CSF accumulation) is a common finding in human ciliopathies and in mouse models with genetic depletion of the multiciliated cell (MCC) cilia machinery. However, the contribution of MCC to CSF dynamics and, the mechanism by which impaired MCC function leads to hydrocephalus remains poorly understood. The aim of our study was to examine if defects in MCC ciliogenesis and cilia-generated CSF flow impact central nervous system (CNS) fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Therefore, the GS is essential for maintaining cerebral fluid homeostasis across the lifespan. A growing number of studies have demonstrated that the impairment of glymphatic transport was associated with several neurological diseases, including cerebral small vessel disease (cSVD) [3][4][5][6], Alzheimer's disease (AD) [7,8], hydrocephalus [7,9], diabetes [10,11], traumatic brain injury [12,13] and stroke [14,15]. Additionally, GS dysfunction is related to sleep disorder as well as tau and beta-amyloid (Aβ) protein accumulations, which underlie the pathogenesis of cognitive impairment and dementia [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the GS is essential for maintaining cerebral fluid homeostasis across the lifespan. A growing number of studies have demonstrated that the impairment of glymphatic transport was associated with several neurological diseases, including cerebral small vessel disease (cSVD) [3][4][5][6], Alzheimer's disease (AD) [7,8], hydrocephalus [7,9], diabetes [10,11], traumatic brain injury [12,13] and stroke [14,15]. Additionally, GS dysfunction is related to sleep disorder as well as tau and beta-amyloid (Aβ) protein accumulations, which underlie the pathogenesis of cognitive impairment and dementia [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Following these foundational DCE-MRI studies in rats, interest in evaluating glymphatic function in mice is rapidly growing, largely due to the availability of genetically manipulated mouse models. 3,6,11,[21][22][23][24][25] Assessing mouse glymphatic function by DCE-MRI has been challenged by the small size of a mouse brain and the limited volume (<20 μL) of fluids that can be delivered intracisternally without significantly altering the intracranial pressure (ICP). 16,26 Early studies on mice used the protocol of administering contrast agent on the bench to allow close monitoring of the infusion process and to visually ensure proper sealing of the infusion site.…”
Section: Introductionmentioning
confidence: 99%
“…Following these foundational DCE-MRI studies in rats, interest in evaluating the glymphatic function in mice grows rapidly due to the availability of genetically manipulated mouse models 3,6,11,[21][22][23][24][25] . Assessing mouse glymphatic function by DCE-MRI has been challenged by the small size of a mouse brain and the limited volume (<20 μL) of fluids that can be delivered intracisternally without significantly altering the intracranial pressure (ICP) 15,26 .…”
Section: Introductionmentioning
confidence: 99%
“…This is not entirely correct. For instance, net movements of CSF through the ventricles are affected to some extent by the beating of cilia on cells of the ependymal lining [ 508 , 509 ]. The effects of cilia are largest close to the lining ependymal layer where they are located relative to those throughout the volume of the CSF containing spaces [ 510 ].…”
mentioning
confidence: 99%